Joint use of data and modeling in coastal wave transformation - Fortes, Conceição Juana (2019)
In the framework of a research project entitled “BRISA—BReaking waves and Induced SAnd transport”,a methodology was devised to characterize the waves joining together in-situ measurements and numerical wave propagation models. With this goal in mind, a number of in-situ measurements were made, for selected positions in front of Praia de Faro (South Portugal), during four days (25th to 28th March, 2009) by using different types of equipments (e.g., resistive wave gauges, pressure sensors, currentmeters and a new prototype pore pressure sensor using optical fibre). Wave records were obtained simultaneously offshore (at a water depth of 11.7 m below mean sea level, MSL) and at the surf and swash zones. The data processing and analysis were made by applying classical time domain techniques. Numerical simulations of the wave propagation between offshore and inshore for the measurement period were performed with two numerical models, a 1D model based on linear theory and a nonlinear Boussinesq-type model, COULWAVE, both forced by the measured offshore wave conditions of 27th March 2009. Comparisons between numerical results and field data for the pressure sensors placed in the surf and swash zones were made and discussed. This approach enables to evaluate the performance of those models to simulate those specific conditions, but also to validate the models by gaining confidence on their use in other conditions.